Empowerment of Women Farmer Groups in Utilization of Idle Land - Casminih Casminih (Borong Newinera Publisher, 2023)
Unused land in Indonesia can be found everywhere, especially on the big islands. Unutilized land is also found in rural areas. In fact, idle land should not be wasted land. If handled properly, it will be able to improve the community's economy. On the other hand, women in rural areas have a lot of free time because they are usually not tied to a permanent job. Utilizing idle land by empowering women who are members of the Women Farmer Group, is the strategy that will be applied in this research. The purpose of this study is to describe the use of unused land in the surrounding environment through community empowerment, namely a group of women. The Farmer Women's Group in Gadog Cianjur Village is the empowered community in this study. The research method used is descriptive with a qualitative approach. How women are empowered to cultivate idle land to produce benefits for people's lives, will be described step by step. The women's spare time (Women Farmers Group) is put to good use by cultivating idle land in their village. Unused land that initially did not produce anything, can eventually be used as a place to grow vegetables. The results of cultivating on unused land which were worked on by these women, had an impact on increasing the family's economy and better social relations.